2016
DOI: 10.1002/pbc.26085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical events in a large prospective cohort of children with sickle cell disease in Nagpur, India: evidence against a milder clinical phenotype in India

Abstract: SCD-related complications are more frequent in Indian children than that observed in CSSCD. Further study is indicated to define SCD phenotype in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These advances appeared to be associated with a reduction in mortality [ 59 , 62 ] and stroke incidence in children appeared to decrease in some regions of the USA and Europe during the 1980s and 1990s [ 24 , 37 , 62 , 64 ] ( Figure 1 A). However, despite newborn screening, the overall incidence in childhood in other areas was similar to that reported previously [ 2 , 27 ], with 0.67/100 PYO at the Children’s hospital of Philadelphia from 1990 to 1998 [ 65 ], 0.85/100 PYO in the Dallas cohort from 1983 to 2002 [ 59 ], 0.88/100 PYO in Northern California from 1991 to 1998 and 0.8/100 PYO in Nagpur, India from 2008 to 2012 [ 66 ] ( Figure 1 A).…”
Section: Strokesupporting
confidence: 87%
“…These advances appeared to be associated with a reduction in mortality [ 59 , 62 ] and stroke incidence in children appeared to decrease in some regions of the USA and Europe during the 1980s and 1990s [ 24 , 37 , 62 , 64 ] ( Figure 1 A). However, despite newborn screening, the overall incidence in childhood in other areas was similar to that reported previously [ 2 , 27 ], with 0.67/100 PYO at the Children’s hospital of Philadelphia from 1990 to 1998 [ 65 ], 0.85/100 PYO in the Dallas cohort from 1983 to 2002 [ 59 ], 0.88/100 PYO in Northern California from 1991 to 1998 and 0.8/100 PYO in Nagpur, India from 2008 to 2012 [ 66 ] ( Figure 1 A).…”
Section: Strokesupporting
confidence: 87%
“…This reinforces the importance of regional context in analysis of SCD mortality as well the significance of longitudinal studies over time. For instance, extreme weather conditions and rainy season are likely to cause higher morbidity and mortality among children in India, implying regional variations ( 30 , 31 , 32 ). Despite robust evidence about gendered inequalities in nutrition, access to healthcare and related higher infant/female mortality ( 10 ), a gender bias is not consistent in our and other hospital-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…As an increasing number of children with SCD are surviving into adulthood, we argue for a shift in policy focus to improving long -term clinical care and supporting their educational and employment needs. New-born screening alongside an intensive follow-up care plan have shown promising results both at GMCH Hospital, Nagpur ( 30 , 40 ) and in some of the remote, rural adivasi areas such as Gudalur ( 27 ) and South Gujarat ( 25 ) as elsewhere in low and middle income countries across the world ( 41 ). Digital technology, remote clinical networks and better professional and patient education can all contribute to improving outcomes of care, as highlighted recently by the Lancet Hematology Commission on SCD ( 2 ).…”
Section: Concluding Observationsmentioning
confidence: 99%
“…However, decades of controlled clinical research have shown that HU, a potent ribonucleotide reductase inhibitor, is both safe and efficacious for SCA and leads to reduced morbidity and mortality, leading to its increasing use to treat both children and adults with SCA in high-resource countries as well as Africa and India. 4 , 7 , 8 , 9 , 10 , 11 , 12 Long-term administration of HU for patients with SCA induces the production of fetal hemoglobin (HbF), which inhibits erythrocyte sickling, improves red cell rheology, and increases red blood cell lifespan. 13 The regions of sub-Saharan Africa and India with a high incidence of SCA are also associated with the highest malaria burden.…”
Section: Introductionmentioning
confidence: 99%